Pentingnya Eksekusi Kepemimpinan Strategis Dalam Mencapai Tujuan Perusahaan: Chapter Review Dari Buku The Strategic Leader’s Roadmap - Taufiq Rahmat; Taufiq Rahmat (Program Studi Manajemen, Universitas Al Ghifari, 2023)
Objective: This article aims to explore the importance of effective strategy execution in achieving organizational goals and draws insights from the case study of H. Lawrence Culp Jr. and the strategy-led execution at Danaher Corporation. The objective is to highlight the key learnings and implications of the study for leaders seeking to enhance their strategic leadership capabilities.Methods: The research employs a case study approach, analyzing the leadership and execution strategies implemented by H. Lawrence Culp Jr. during his tenure at Danaher Corporation. It utilizes secondary data from the book